ANALISIS PENGARUH PENGETAHUAN, SIKAP DAN PERILAKU PERAWAT TERHADAP KEJADIAN INFEKSI NOSOKOMIAL DI RS MITRA KELUARGA SURABAYA - jurnalpps pps; C. Sri Hartati; Gurendro Putro; Hermin ÔÇÄ (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
This study aims to analyze nurses' knowledge, attitudes and behavior towards the incidence of nosocomial infections. This study involved 104 nurses who worked at Mitra Keluarga Surabaya Hospital as a source of data using questionnaires and observation of infection criteria. The variables used in this study were knowledge, attitudes, behavior as independent variables, the incidence of nosocomial infections as controlled variables. The results showed that there were studies of nurses' knowledge, attitudes and behavior towards the incidence of nosocomial infections in the Inpatient Room of Mitra Keluarga Surabaya Hospital and the research conclusions showed that most nurses were wellinformed, good attitude and most of them were well behaved. While at Mitra Hospital in Surabaya, Mitra Keluarga Surabaya Hospital mostly in hospitals did not have infection, simultaneous knowledge, attitudes and problems related to the incidence of infections in inpatient areas at Mitra Keluarga Hospital, Knowledge, attitude and partial simultaneous use of events infection in the inpatient room of Mitra Keluarga Hospital.